Double Chooz and reactor neutrino oscillation : [omega]13 improvement and first effective [delta]m 2/31 measurement /: [omega]13 improvement and first effective [delta]m 2/31 measurement. (2015) - Bezerra, Thiago Junqueira de Castro
No abstract available